XV.-XVI. Yüzyıllarda Isparta Kazası: Nüfus ve Yerleşme - Züleyha USTAOĞLU (Gazi Akademik Bakış)
Isparta which has been known since ancient times and referred as “Seperde” or “Sparda” or “Isparada” in the sources; was the centre town of Hamid Sanjak in the Ottoman Empire in XV. and XVI. century. In this study, the “population” and “settlement” structure of the town will be examined in the light of the three mufassal deed tahrir registry of 1478, 1522 and 1568, in which the Isparta Town was recorded, and the impact of the population situation on settlement will be examined as well.